On the Nature of Harms Reported by those Identifying a Problematic Drinker in the Family, an Exploratory Study - Berends, L.; Ferris, J.; Laslett, Anne-Marie (Springer New York LLC, 2014)
A national telephone survey on alcohol-related harms experienced by others consisted of 2,649 randomly selected adults and 415 (15 %) commented on the family member whose heavy drinking most negatively affected them. Relationships comprised close family (child, parent, sibling; 47 %), partner (22 %), extended family (e.g., aunt/uncle, cousin, grandparent; 19 %), and ex-partner (12 %). Common harms were being emotionally hurt and having a serious argument. An average of 3.4 harms was reported and multiple harms meant a higher likelihood of significant impact. Harms were classified into four domains which accounted for approximately 60 % of the explained variance: psychological (26.1 %), physical (11.4 %), social (10.9 %), and practical (9.6 %). Psychological and practical domains were associated with significant harm as were being female and sharing a home with the drinker. Perceived harms from a problematic drinking family member are broad ranging and have significant impact. Advice, information, and directions for family members dealing with a problematic drinker need development.